Factors Influencing Sleeve Grouting Quality for Prefabricated Building: An Interpretive Structural Modeling Approach - Yingbo Ji; Zihao Zhao; Fuyi Yao; Hong Xian Li; Yanyao Li; Xiaoyun Du (Advances in Civil Engineering)
The defect in quality caused by the noncompactness of sleeve grouting has become the main obstacle restricting the further implementation of the prefabricated building in China. Studies have been conducted to explore the influencing factors of inadequate grouting; however, few studies attempt to investigate the complex interrelationship and lack of systematic cognition among these factors. To fill this gap, this study conducted a comprehensive literature review to collect the influencing factors of sleeve grouting and verified the reliability of these factors using the combined methods of brainstorming and semistructured expert discussion. A total of 18 key factors were identified and determined. The structural interpretation model (SIM) and Matrice d’Impacts Croisés Multiplication Appliquée à un Classement (MICMAC) approaches were then used to analyze, depict, and explain the internal relationships between the factors. The results indicate that all factors were classified into six levels, among which poor responsibility of supervisors and weather conditions are the most basic factors, while grouting speed and a loose-sealing rubber plug are the most important factors. Finally, a three-level control strategy was proposed to improve the compactness quality of sleeve grouting. The research findings provide valuable guidelines for managers to eliminate the grouting quality defect and to further the development of prefabricated buildings in China.